Pengaruh Diversitas Dewan Direksi dan Profitabilitas terhadap Nilai Perusahaan LQ45 - James Andrian; Temy Setiawan (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Covid 19 and the increase of Fed’s interest rates had an impact on the company’s value. Based from this phenomenon, the company value has a major role in changing the perception of the shareholders. This study is intended to show empirical evidence related to the effect of board of directors’ diversity, profitability, and growth opportunity on firm value. This study’s data uses LQ45 companies from 2018-2021 listed on the Indonesia Stock Exchange (IDX). The research method is panel data regression. The results of this study conclude that there is no effect of the board of directors' diversity and growth opportunity on firm value. On the other hand, profitability has a positive influence on firm value. This study provides an opportunity for future researches to expand their knowledge’s and as a reference material.